A busca pela anatomia na "crítica da terra": estado e sociedade civil-burguesa na obra de Karl Marx entre 1843 e 1844 - Lucas de Oliveira Maciel (2021)
Between 1843 and 1844, not long after his first great reckoning with Hegel’s thought, Karl Marx, armed with the theoretical conquest that, in the relation between the State and civil-bourgeois society, the latter is the subject of which the former is the predicate, moves forward in his reflections in texts which would only be published the following year. If, until then, his critique had taken him to the defense of democracy, conceived in terms of a society that is immediately political, such perspective is very soon abandoned. However, the author does not come immediately to the conclusion that, as he would write the following decade, the anatomy of civil-bourgeois society is in political economy. Despite this, three texts written in this period mark the beginning of a critique that would reach not only the polítical State, now conceived as the full form of political power, but also civil-bourgeois society. Treated as two sides of the same coin, State and civil-bourgeois society become the object of analysis, and, even in their modern forms, as spheres that must be supressed. Even if, in his writings of the time, Marx had to take german reality and its anachronism as the starting point, the author always refers to more advanced societies, and becomes a critic of modern society and of the modern State. Moreover, if, on one hand, the texts analysed in the present study have already been object of different studies, by different authors, on the other hand, there are still gaps to fill and mistakes to correct. There are authors which, because they attribute to the Marx of 1843-1844 the label of “young Marx”, make interpretative mistakes of his work of the time. Still, beyond Marx critique of the State and of political power in general, the other side of the relation has been little explored: civil-bourgeois society. Even if he had still much to develop in the economic field, the thinker begins, already at this time, the search for the categories that rule civil-bourgeois society. The latter is described as a sphere ruled by money, by the great industry, by private property, by commerce, and by social classes. Therefore, Marx treats many of its aspects. His defense of social revolution is inseparable not only from the supression of the State, but, at the same time, from the supression of its basis, civil-bourgeois society.